2023
DOI: 10.1515/ijfe-2022-0181
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of thermal sterilization heating process of canned fruits with different shapes based on UDM and RDM

Abstract: The random distribution model (RDM) and uniform distribution model (UDM) were used to simulate the thermal sterilization of canned fruit. The RDM was established with the radiation function, and the stability of RDM results was analyzed by simulating temperature change during thermal sterilization and determining the sterilization parameter F value of the slowest heating zone (SHZ). The performance of the distribution models in simulating thermal sterilization heating process of canned fruit with different sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It was also found that the SHZ displaced towards the bottom of the can and eventually stayed in a region about 10–15% of the can height from the bottom. Fu et al (2023) numerically studied the thermal sterilization of canned fruits of different shapes based on uniform and random distribution (RDM) models. The findings of several RDM simulations were consistent with temperature changes and lethality levels, indicating that the RDM‐based simulation results were stable.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the SHZ displaced towards the bottom of the can and eventually stayed in a region about 10–15% of the can height from the bottom. Fu et al (2023) numerically studied the thermal sterilization of canned fruits of different shapes based on uniform and random distribution (RDM) models. The findings of several RDM simulations were consistent with temperature changes and lethality levels, indicating that the RDM‐based simulation results were stable.…”
Section: Introductionmentioning
confidence: 99%